Tobacco use and khat chewing among adolescents in Yemen: a large-scale school-based cross-sectional study - Sadeq Ali Al-Maweri; Mohammed Nasser Alhajj; Walid A. Al-Soneidar; Anas Shamala; Baleegh Abdulraoof Alkadasi; Abdullah Ghalib Amran; Faisal Abu-lohom; Hesham Mohammed Al-Sharani; Mohammed Abdullah Basalamah; Zakarya Al-Muaalemi; Asma Saleh Almeslet; Saleem Abdulrab; et al. (BMC, 2024)
Abstract Objective The present study sought to assess the prevalence and determinants of tobacco use (cigarette smoking and shisha use) and khat chewing among Yemeni adolescents, and to evaluate their knowledge and attitudes toward these habits. Methods This school-based cross-sectional study was conducted among 13 to 19-year-old students attending middle/high schools (both private and public) across five main cities in Yemen. Data were collected using self-administered questionnaires comprising questions/items related to sociodemographic data, cigarette smoking, shisha use, khat chewing, and knowledge on and attitudes toward these habits. Bivariate and multivariate analyses were used to explore the most determinant factors. Results A total of 7505 students were recruited from 42 schools across five major cities in Yemen. The prevalence rates of khat chewing, cigarette smoking, and shisha use were 42.4%, 6.8%, and 19.3%, respectively. Compared to females, male subjects reported significantly higher prevalence of khat chewing (51.4% vs. 23.5%, p < 0.001), shisha use (20.3% vs. 17.2%, p < 0.01), and cigarette smoking (8.8% vs. 2.6%, p < 0.001). Male gender, older age, poor knowledge, khat chewing, parents' low education level, and parents' and peers' smoking habits were significant determinants of adolescents' cigarette smoking status. Private education, male gender, older age, poor knowledge, parents' low education level, and parents' and peers' khat chewing habits were significant determinants of adolescents' khat chewing status. The participant's knowledge of and attitudes toward tobacco use and khat chewing were inadequate. Conclusion The prevalence of khat chewing, shisha use, and to lesser extent cigarette smoking among Yemeni adolescents is high that needs immediate intervention. The results highlight the urgent need to implement prevention strategies to tackle these habits among the youth in Yemen.